IMPROVING THE QUALITY OF A PERITONEAL DIALYSIS SERVICE: LEARNING FROM EXPERIENCE. Issue 1 (7th March 2013) - Kazancioglu, Rumeyza
SUMMARY Background Different trends in peritoneal dialysis (PD) utilisation are observed all over the world. The primary aim of all of these dialysis programmes is to provide a quality service to the patients, which depends in part in careful planning of the structure and organisation of the dialysis unit. Aim The aim of this paper is to review the available literature on the development and evaluation of PD programmes and to provide recommendations about how to start a new PD unit. Findings The essentials of a quality PD service are pre‐dialysis education and timely start on dialysis, adequate training for the physicians and nurses, full support from complementary disciplines, effective programme size and continuous quality improvement strategies. Those working in PD should make maximum use of limited resources to improve their dialysis programme penetration as well as clinical outcomes.